MPEG-4 3D Graphics: from specifications to the screen - Celakovski, Sashko; Preda, Marius; Kalajdziski, Slobodan; Davchev, Dancho; Preteux, Françoise (My University, 2006)
This paper presents a novel implementation of a 3D rendering engine able to display 3D graphics MPEG-4 objects. By using the MPEG-4 SDK (Software Developer Kit), the 3D objects are first decoded and the MPEG-4 scene graph structure is filed. We introduce a scene manager able to address in an optimized manner the rendering requirements. It is developed as part of the rendering engine and it enables to create an appropriate form representation of the data resources. The novel concept implemented here is to consider the scene management with respect to the rendering constraints and not to the representation of the data as in a usual MPEG-4 approach. This paper describes the software communication procedures between the MPEG-4 SDK and the rendering scene management in the case of static and animated (skinned) object and some results dealing with the representation of an articulated model illustrate the performances of the developed approach.
Keywords: 3D Graphics, MPEG-4 Standard, Rendering Engine, Software Developer Kit